Differential eNOS-signalling by platelet subpopulations regulates adhesion and aggregation. Issue 14 (4th September 2017) - Radziwon-Balicka, Aneta; Lesyk, Gabriela; Back, Valentina; Fong, Teresa; Loredo-Calderon, Erica L; Dong, Bin; El-Sikhry, Haitham; El-Sherbeni, Ahmed A; El-Kadi, Ayman; Ogg, Stephen; Siraki, Arno; Seubert, John M; et al.
Abstract: Aims: In addition to maintaining haemostasis, circulating blood platelets are the cellular culprits that form occlusive thrombi in arteries and veins. Compared to blood leucocytes, which exist as functionally distinct subtypes, platelets are considered to be relatively simple cell fragments that form vascular system plugs without a differentially regulated cellular response. Hence, investigation into platelet subpopulations with distinct functional roles in haemostasis/thrombosis has been limited. In our present study, we investigated whether functionally distinct platelet subpopulations exist based on their ability to generate and respond to nitric oxide (NO), an endogenous platelet inhibitor. Methods and results: Utilizing highly sensitive and selective flow cytometry protocols, we demonstrate that human platelet subpopulations exist based on the presence and absence of endothelial nitric oxide synthase (eNOS). Platelets lacking eNOS (approximately 20% of total platelets) fail to produce NO and have a down-regulated soluble guanylate cyclase-protein kinase G (sGC-PKG)-signalling pathway. In flow chamber and aggregation experiments eNOS-negative platelets primarily initiate adhesion to collagen, more readily activate integrin αIIb β3 and secrete matrix metalloproteinase-2, and form larger aggregates than their eNOS-positive counterparts. Conversely, platelets having an intact eNOS-sGC-PKG-signalling pathway (approximately 80% of total platelets) form the bulk of an aggregate via increased thromboxane synthesis and ultimately limit its size via NO generation. Conclusion: These findings reveal previously unrecognized characteristics and complexity of platelets and their regulation of adhesion/aggregation. The identification of platelet subpopulations also has potentially important consequences to human health and disease as impaired platelet NO-signalling has been identified in patients with coronary artery disease.